Bioactivities of Prosopis africana Whole Fruit: Antibacterial and Urease Inhibition Properties - Kayode Muritala Salawu; Saad Toyin Abdullahi; Akeem Ganiyu Rabiu; Olutosin Alarape Adegboye; Muhammad Aamer; Nuzhat Shehla; Yan Wang (Biology, Medicine, & Natural Product Chemistry, 2025)
Prosopis africana (Guill. & Perr.) Taub. (Fabaceae) is a West African tree traditionally used for treating infections. However, a systematic evaluation of the bioactivities of its fruit remains limited, and studying the fruit offers a more sustainable and conservation-friendly approach compared to harvesting the bark or roots. This study aimed to investigate the antibacterial and urease inhibitory properties of the whole fruit extract of P. africana and its solvent-partitioned fractions. The powdered whole fruit was macerated in 70% methanol to obtain a crude extract (PAF-0). A 1.1 kg portion of PAF-0 was subsequently partitioned using 1 L volumes per cycle into n-hexane (PAF-1), dichloromethane (PAF-2), ethyl acetate (PAF-3), and aqueous (PAF-4) fractions. Antibacterial activity was evaluated against Gram-positive and Gram-negative bacteria using the Microplate Alamar Blue Assay (MABA). Jack bean urease inhibition was assessed spectrophotometrically. All experiments included vehicle controls (DMSO) and were performed with three independent replicates (n=3). The dichloromethane fraction (PAF-2) exhibited the strongest antibacterial activity, showing 84% and 88% inhibition against Escherichia coli and Salmonella typhi, respectively, which was comparable to the standard drug ofloxacin. In the urease inhibition assay, the n-hexane fraction (PAF-1) and the crude extract (PAF-0) were the most potent, with IC50 values of 27.1 µg/mL and 27.6 µg/mL, respectively. The findings indicate that the dichloromethane and n-hexane fractions of P. africana fruit possess significant antibacterial and urease inhibitory activities. This provides a scientific basis for its traditional uses against infections and highlights its potential as a rich source of bioactive compounds for further pharmacological development.